Pengaruh Gaya Belajar terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas XI SMA Negeri 1 Kedungreja Kabupaten Cilacap - Rahmawati, Febia; Praptanti, Isnaeni (RUANG KATA: Journal of Language and Literature Studies, 2023)
Education is essential for every individual, driving many to seek the best and highest level of learning possible. Learning styles play a crucial role in academic success by enhancing the effectiveness of the learning process. Each individual's learning style varies from another based on their comprehension and retention of lessons taught by educators. Despite their efforts, some students struggle to grasp lessons, while others diligently study yet perform sub-optimally in exams. Such achievements may result from not identifying a compatible learning style that allows them to assimilate the content efficiently. This research aims to determine the effect of Learning Styles on Indonesian Language Learning Achievement of Grade XI Students at SMA Negeri 1 Kedungreja, Cilacap District. Therefore, this study employs a quantitative method, and the collected data are then interpreted to yield descriptive information. Data collection techniques include questionnaires, and linear regression is used for data analysis. The research findings indicate a correlation value of 0.932. The effect (R Square) of learning styles on learning achievement is 86.8%, with the remaining 13.2% affected by unexamined variables. A strong relationship between Learning Styles and Learning Achievement is evident, as the significance value is 0.05 with a Pearson correlation value of 0.932. In essence, the relationship is robust. Keywords: Learning Styles, Learning Achievement, Indonesian Language.